2017
DOI: 10.4187/respcare.05102
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cisatracurium Versus Atracurium in Early ARDS

Abstract: Seventy-six subjects with ARDS were included in the study. Eighteen subjects (24%) were treated with atracurium, whereas 58 (76%) were treated with cisatracurium. Equivalent dosages of sedation and analgesia as well as use of brain function monitoring technology were similar between both groups. There were no differences in clinical outcomes. Specifically, improvement of P /F was a median (interquartile range [IQR]) of 65 (25-162) in the atracurium group and 66 (IQR 16-147) in the cisatracurium group ( = .65).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
2
15
0
1
Order By: Relevance
“…In a retrospective study, cisatracurium was not superior to atracurium [89]. In contrast, the duration of mechanical ventilation and the length of ICU stay were slightly but significantly shorter in patients with or at risk of ARDS who were treated with cisatracurium, compared with those treated with vecuronium [90].…”
Section: Methodsmentioning
confidence: 99%
“…In a retrospective study, cisatracurium was not superior to atracurium [89]. In contrast, the duration of mechanical ventilation and the length of ICU stay were slightly but significantly shorter in patients with or at risk of ARDS who were treated with cisatracurium, compared with those treated with vecuronium [90].…”
Section: Methodsmentioning
confidence: 99%
“…Although cisatracurium is the only NMBA that has been studied in randomized controlled trials, it is unknown if the benefit is confined to cisatracurium, although one single-center retrospective study that compared atracurium to cisatracurium for severe ARDS found no difference in clinical outcomes. 117 Atracurium, rocuronium, and vecuronium are other intermediate-acting NMBA and can be given as continuous infusion and should be considered in contingency care (Table 4). 112 Pancuronium, a long-acting NMBA, can also be considered for continuous infusion in crisis care.…”
Section: Paralysis Strategies In Covid-19 Patientsmentioning
confidence: 99%
“…It has been reported that paralysis can be continued beyond 48 hours without increasing the overall mortality [35], while whether longer or shorter infusions of NMBA would provide additional bene t or change the prevalence of ICUacquired weakness is unknown. Moreover, when compared with vecuronium [36] or atracurium [37], cisatracurium, used in all of our included trials, was not associated with a difference in mortality, which suggest that those short-term positive outcomes were not cisatracurium-speci c. Thus, a more economical selection of neuromuscular blocking agents in clinical settings should be considered in future.…”
Section: Discussionmentioning
confidence: 76%